A Review of the Macroeconomic Policy Frameworks adopted by the BRICS countries (2000-2015) - Mbangata, Themba; Kanayo, Ogujiuba (Journal of Economics and Behavioral Studies, 2017)
Recent development in the practice of macroeconomic policy has increased the importance of monetary and fiscal policy. Monetary policy within BRICS countries has shifted towards the setting of interest rates as the key monetary instrument, along with the adoption of inflation targets as key monetary policy objectives. It is well accepted that there is no one set of macroeconomic policies that guarantees sustained growth and development in the economy. However, the BRICS countries have been following a similar trend with regard to the exchange rate policy. This is shown by the fact that the BRICS countries have moved away from using a pegged exchange rate regime towards a managed floating exchange rate regime which is in contrast with the recommendations of the Washington Consensus. On the fiscal side, the BRICS countries agreed to spend only what is necessary in order to avoid the ballooning local government debt. Summarily, the BRICS countries have performed well economically and socially although there are still some room for improvement. However, there are still other BRICS members who have government debt that are well above half of their Gross Domestic Product. Alignment of policy regimes would strengthen the macroeconomic base of the BRICS. It is recommended that all BRICS members need prioritise inclusive governance that would checkmate social ills such as poverty, inequality and unemployment, while promoting social inclusion.